Medium to long-term results of a recessed glenoid for glenoid resurfacing in total shoulder arthroplasty. (December 2020) - Ross, Mark; Glasson, Jean-Marc; Alexander, Justin; Conyard, Christopher G; Hope, Benjamin; Jenkins, Owen; Duke, Phillip FR
Background: Recessed mini-glenoid components provide an alternative to total shoulder replacement that may avoid some of the known shortcomings and complications associated with shoulder hemiarthroplasty or standard glenoid components in difficult cases. This study reports survivorship, radiological and clinical outcomes of a recessed mini-glenoid implant in a consecutive cohort. Methods: Retrospective cohort study reporting outcomes of 28 consecutive shoulders (27 patients) following total shoulder replacement using a recessed, cemented mini-glenoid implant at two sites. Results: The most frequent diagnosis was primary osteoarthritis (79%); glenoid morphology was Walch Type A (67%), B1 15%, B2 10% and C 10%. At final follow-up, pain was 16.3 (SD = 23.1), American Shoulder and Elbow Score was 64.5 (SD = 31.9) and (normalized) Constant score was 83.0 (SD = 20.7). Implant survivorship at average final follow-up of seven years (3–13) was 96.4%. Seven mini-glenoids showed small peripheral radiolucent lines at one-year X-ray follow-up but were non-progressive on subsequent imaging. Discussion: Recessed polyethylene mini-glenoid is an attractive alternative for shoulder arthroplasty and provides an intermediate solution between standard glenoid components and hemiarthroplasty. Our medium to long-term results demonstrate reliable clinical outcomes, absence of glenoid erosion, low complication rate and satisfactory implant survivorship.